TEAM BUILDINGTHROUGH CLASS BLOG - Lestari, Febriyanti Dwiratna (Journal of English and Education (JEE), 2010)
Student's work for a writing class is no longer one submitted for limited readership the teacher and the writer himself as it can be publicly shared online. Posted on a webpage such as blog, it allows more people to access, read, or leave comments. Though it may sound intimidating for some shy students who are likely to keep their writing private, it is less about trespassing the confidential status of a student's work than building the student's self confidence and encouraging them to produce a better composition. It is especially through class blog which is managed by a number of students of the same class. This model proves to be beneficial for the students because not only is their writing read by more audience than their fellow classmates but they can also identify themselves as a team. This paper attempts to describe the previous researches concerning the application of blog in general and what it means by class blog, the model of class blog which has been implemented in this project, and how team work among the classmates is built through class blogs.